The role of central banks in financial stability: how has it changed? - Evanoff, Douglas Darrell; Holthausen, Cornelia; Kaufman, George G.; Kremer, Manfred (Singapore World scientific publishing, 2014)
The two most topical issues in current financial markets deal with the causes of the recent financial crisis and the means to prevent future crises. This book addresses the latter and stresses a major shift in most countries toward a better understanding of financial stability and how it can be achieved.
"The participants at the Fourteenth Annual Federal Reserve Bank of Chicago International Banking Conference, co-sponsored with the European Central Bank in Chicago on November 10-11, 2011, reevaluated the role of central banks in financial stability ... This volume contains the paper and panel presentations at the conference, including the keynote addresses by major policymakers and practitioners in the United States and abroad."--Page ix.
Includes bibliographical references.
oif 11/06/15
Loan
Keywords: Banks and banking, Central; Financial crises